2011
DOI: 10.1021/ja207551f
|View full text |Cite
|
Sign up to set email alerts
|

Formation of C–C and C–O Bonds and Oxygen Removal in Reactions of Alkanediols, Alkanols, and Alkanals on Copper Catalysts

Abstract: This study reports evidence for catalytic deoxygenation of alkanols, alkanals, and alkanediols on dispersed Cu clusters with minimal use of external H(2) and with the concurrent formation of new C-C and C-O bonds. These catalysts selectively remove O-atoms from these oxygenates as CO or CO(2) through decarbonylation or decarboxylation routes, respectively, that use C-atoms present within reactants or as H(2)O using H(2) added or formed in situ from CO/H(2)O mixtures via water-gas shift. Cu catalysts fully conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 50 publications
6
37
0
Order By: Relevance
“…Henceforth, conversions and selectivities are based on the formation of products from this equilibrated reactant lump. Cu surfaces can catalyze aldol condensation and esterification of 1-propanol-propanal reactants [50], which form products identical to those observed on TiO 2 (P25) + Cu/SiO 2 mixtures (Table 1). These rates on Cu surfaces, however, are >10-fold lower than those on TiO 2 (P25) catalysts at all conditions used here; such Cu contributions were subtracted from reported rates on TiO 2 (P25) + Cu/SiO 2 mixtures when so required.…”
Section: Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…Henceforth, conversions and selectivities are based on the formation of products from this equilibrated reactant lump. Cu surfaces can catalyze aldol condensation and esterification of 1-propanol-propanal reactants [50], which form products identical to those observed on TiO 2 (P25) + Cu/SiO 2 mixtures (Table 1). These rates on Cu surfaces, however, are >10-fold lower than those on TiO 2 (P25) catalysts at all conditions used here; such Cu contributions were subtracted from reported rates on TiO 2 (P25) + Cu/SiO 2 mixtures when so required.…”
Section: Methodsmentioning
confidence: 63%
“…These molecules are the expected products from primary and secondary propanal condensation events (Scheme 2) [50]. Their unsaturated nature and the absence of 1-propanol, even in the presence of H 2 , indicate that TiO 2 (P25) cannot catalyze C@C or C@O hydrogenation via either H 2 activation or H-transfer pathways at these reaction conditions.…”
Section: Oxygenate Reactions On Tio 2 and Cuatio 2 Catalystsmentioning
confidence: 99%
“…Acetaldehyde could undergo steam reforming by reacting with water molecules produced from the two dehydration reactions. Indeed, previous studies of other silica‐supported metal oxides showed that mainly hydrogen and carbon dioxide, with trace amounts of CH 4 , CO, and propylene, could be produced . This is supported by the detection of CO 2 in the outlet stream by GC‐TCD, as well as 0.5 and 1.7 % of CH 4 at higher reaction temperatures of 450 and 500 °C, respectively, for the 5V/SiO 2 catalyst.…”
Section: N2 Physisorption Data Nh3‐tpd Data Acid Site Densities Anmentioning
confidence: 99%
“…Copper nanoparticles are good catalysts for important industrial processes such as alcohol synthesis, 16,17 water gas shift, 18 deoxygenation of biomass-derived molecules, 19 selective alkyne hydrogenation, 20 or CO electroreduction to liquid fuels, 21 and in some of these reactions, in particular in the case of selective hydrogenations, the catalytic activity has been specifically attributed to small copper clusters. 22 For this reason, copper clusters are currently a hot subject of research, 23,24 and several quantum chemical studies concerning the structure and electronic nanoparticles are placed in a unit cell that is periodically repeated in the three dimensions of space, and that employ plane wave basis sets within a reciprocal space representation that lead to a reduction in the computational scaling to N 2 or even N. [44][45][46] A key advantage of this approach is that small, intermediate size and large transition metal clusters or nanoparticles, as well as the upper size limit represented by extended surfaces, can be studied using a single methodology.…”
Section: Introductionmentioning
confidence: 99%